2016
DOI: 10.5114/cipp.2016.62701
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in eyewitness identification accuracy between sequential and simultaneous line-ups: consequences for police practice and jury decisions

Abstract: backgroundAlthough previous research has indicated that sequential line-up procedures result in fewer mistaken identifications, this was found to be at the expense of accurate identifications more typical within simultaneous procedures. Hence, there remains a lack of agreement about which procedure is superior, and the interaction such procedures have with eyewitness confidence. The interaction between witness demographics and identification accuracy also remains unclear. participants and procedureThe opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The current literature surrounding eyewitness behaviour is extensive and continuously expanding with insightful and novel findings (e.g. McWilliam and Mojtahedi 2018; Willmott and Sherretts 2016). The present study contributed to this field of research by attempting to identify whether eyewitnesses would use available information about their cowitnesses to gauge the validity of their statements.…”
Section: Resultsmentioning
confidence: 95%
“…The current literature surrounding eyewitness behaviour is extensive and continuously expanding with insightful and novel findings (e.g. McWilliam and Mojtahedi 2018; Willmott and Sherretts 2016). The present study contributed to this field of research by attempting to identify whether eyewitnesses would use available information about their cowitnesses to gauge the validity of their statements.…”
Section: Resultsmentioning
confidence: 95%
“…Generalising research from one gender to the other may lead to training programs developed that are only of actual value when applied to males. With recent research in witness identification accuracy displaying the evidential value of prior training (Willmott and Sherretts, 2016), future research should seek to further explore the role of individual differences within the target, central to detecting deception research.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some of the above studies have found gender differences and offered various explanations for this, other researchers did not obtain any such findings (e.g., Butts et al, 1995;Wells & Olson, 2003;Willmott & Sherretts, 2016). Therefore, it is evident that there is considerable inconsistency in previous research.…”
Section: Introductionmentioning
confidence: 86%
“…These conditions can be considered as a limitation of this study because of real-life eyewitnesses observe crimes in different environments and conditions. (Willmott & Sherretts, 2016).…”
mentioning
confidence: 99%